Association of SMuRFs with cardiovascular risk factors, disease burden, and pharmacological management in Middle Eastern patients with ASCVD and a family history of premature CVD - Alrida, Nour Ali; Albikawi, Zainab; Alotaibi, Nader; Alkouri, Osama; Saifan, Ahmad Rajeh; Jarrah, Mohamad; Hammoudeh, Ayman; Khader, Yousef; Alenezy, Awwad; Al-Zu’bi, Basheer M.; Alharbi, Abdulhafith; Alhalaiqa, Fadwa; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionCardiovascular diseases (CVDs) are considered the main reason for death around the world. This study investigated the impact of standard modifiable risk factors (SMuRFs) on cardiovascular risk, disease severity, and treatment patterns in Middle Eastern patients who have a history of premature cardiovascular disease, with outcomes including acute coronary syndrome and cerebrovascular accidents.MethodsWe analyzed data from six established cardiovascular registries and the Jordan SMuRF-less cohort study. All datasets were integrated into a single harmonized database to ensure consistency in variable definitions and measurement. The combined dataset included standardized information on participants' demographic and clinical characteristics, cardiovascular risk factors, comorbidities, medication use, and one-year outcomes among individuals categorized as having 0, 1–2, or 3–4 Standard Modifiable Risk Factors (SMuRFs). In total, data from 1,859 participants with atherosclerotic cardiovascular disease (ASCVD) and a family history of early cardiovascular disease were included in the final analysis.ResultsAge varied among the groups. The youngest group (G1) had a mean age of 51.9 ± 12.7 years, while the oldest group (G3) had a mean age of 57.1 ± 10.1 years (p < 0.001). CKD and heart failure were more prevalent in the upper SMuRF groups (p < 0.001 and p < 0.05, respectively). BMI and triglycerides rose with rising SMuRFs (p < 0.001), and LDL levels differed between groups (p < 0.01). Medication use was highest in G3, especially for statins (94.8% vs. 87.5%), beta blockers (76.0% vs. 66.7%), and oral hypoglycemics (28.6% vs. 2.1%).ConclusionThe study highlights the significant impact of SMuRFs on cardiovascular health. Older patients with a higher burden of SMuRFs show worse lipid profiles and increased medication use. Given the high prevalence of metabolic syndrome and diabetes in the region, targeted interventions, including lifestyle changes and early pharmacological management, are essential for reducing CVD risk in Middle Eastern populations.Clinical Trial RegistrationClinicalTrials.gov, NCT06199869.